Rola Chin w procesie transformacji systemu międzynarodowego Azji Wschodniej - Sokola, Paweł (The Chinese role in transformation of the East Asian international system, 2009)
The East Asian international order is in the course of dramatic changes. One can argue that its scale and dynamics result directly from the strategic decision of the PRC leadership to integrate the country with the regional order created under the US patronage. The purpose of this paper is to outline basic characteristics of this order, its historical background as well as presenting the context of the major shift in Beijing’s policy towards its international environment. The author’s main thesis is that, as the latest developments are indicating, the regional system of power and influence distribution is on the verge of much deeper and throughout transformation than the one observed to date. It may be accomplished through mounting pressures for the regional integration, multilateral diplomatic efforts or strategic dialog of the region’s two greatest powers. What seems to be imminent however, is the growing awareness of the need for reconstructing the East Asian international framework - remaking the set of rules established decades ago
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67